Evaluation of palm oil mill effluent treatment with concomitant phenolics production by aspergillus niger IBS-103ZA - Idris, Zulkarnain Mohamed; Jamal, Parveen; Alam, Md Zahangir (INSI Publications, 2012)
Previous results show that fermentation of palm oil mill effluent (POME) with Aspergillus niger IBS-103ZA has successfully increased the phenolic content (from 856±2.22 to 941±3.72 GAE mg/l) and also antioxidant activity of the extract (with IC50 value of 0.45 mg/ml compared to unfermented extract with IC50 value of 1.13 mg/ml based on DPPH radical scavenging assay). In this study, the potential use of Aspergillus niger IBS-103ZA to treat the effluent for removal of chemical oxygen demand (COD) and heavy metals were evaluated. The percentage of COD removal was low. Only 24.44% of COD was removed after 120 hours of fermentation period. The biomass of Aspergillus niger IBS-103ZA absorbed Pb2+ ions from POME more rapidly than Zn2+ ions. Within 24 hours of fermentation period, the percentage removal of Pb2+ ions was 76.08%. The Pb2+ ions were totally removed after 72 hours of fermentation period. The removal of Zn2+ ions from POME was not as efficient as Pb2+ ions. Only 24.79% of Zn2+ ions were removed after 120 hours of fermentation period. No Cd was detected in POME during the study. The highest phenolics production (949.56±3.82 GAE mg/l) and total protein (76.58±0.43 g/kg-dried biomass) were obtained at 72 and 48 hours of fermentation respectively. Thus, POME treatment via fermentation with Aspergillus niger IBS-103ZA not only increased the amount of its value added product but also reduced the pollution load in the effluent.